Relationship between Psychosocial Impairment, Food Choice Motives, and Orthorexic Behaviors among Polish Adults - Plichta, Marta (Nutrients, 2020)
Orthorexic behaviors correlate not only with health motives when choosing food but may also coexist with psychosocial impairment. The aim of this study was to assess the motives of food choice and psychosocial impairment among adults with orthorexic behaviors through the use of ORTO-15 and ORTO-7. The data for the study were collected from a sample of 1007 Polish adults through a cross-sectional quantitative survey conducted in 2019. The respondents were asked to complete the ORTO-15 questionnaire, the Food Choice Questionnaire (FCQ), and the Clinical Impairment Assessment (CIA). Orthorexic behaviors were measured using both the 15-item and the shorter 7-item version of the ORTO questionnaire. To determine the factors coexisting with the orthorexic behaviors, linear regression models were developed. The scores of both ORTO-15 and ORTO-7 correlated positively with the global CIA scores and the scores of personal, cognitive, and social impairments, but compared to the ORTO-7 scores, the ORTO-15 scores showed weaker correlations with the global CIA score and individual CIA scales. Orthorexic behaviors measured with ORTO-15 correlated positively with such food choice motives as health, natural content, and weight control; whereas orthorexic behaviors measured with ORTO-7 showed positive bivariate correlations only with two food choice motives: health and weight control. In regression models, sensory appeal, age, and education lower than secondary were associated inversely with orthorexic behaviors measured by both the ORTO-15 and the ORTO-7. In conclusion, the obtained results confirm that orthorexic behaviors are associated with a higher score regarding health motivation and cause an increase in psychosocial impairment. In addition, orthorexic behaviors are associated with greater importance of body weight control, which confirms the relationship between orthorexic behaviors and other eating disorders (ED), such as anorexia nervosa (AN) and bulimia nervosa (BN). However, similar motives for food choice displayed by the groups with higher scores of the ORTO-15 and the ORTO-7 and strong correlation between results obtained from both tools confirmed the similarity between these two questionnaires, thus revealing the weak psychometric properties also of the shorter seven-item version of the ORTO. Future studies on food motives, psychosocial impairment, and orthorexic behaviors should consider using other tools for measuring orthorexic behaviors.